Z problematyki badań nowożytnych kopców w rejonie Mrągowa w świetle wykopalisk w Notyście Wielkim - Marciniak-Kajzer, Anna (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
Examinations of cone-shaped mound forms have a long tradition in our country. Cone- -shaped mounds have attracted archaeologists for years and have been a subject of their deep attention and investigations. It often happens that the shape of these objects does not remind the form of a cone from which their name was derived. Also contrary situations happen when ideally regular, classic cone-like forms cover a completely different content. The above work is an attempt to outline this issue. A cone-shaped mound in Notyst Wielki, a subject of stationary excavations, so far identified as a cone shaped stronghold is undoubtedly an anthropomorphic object. Unfortunately, neither its origin nor a function it was supposed to fulfil has been defined. What can be definitely staled is that its origin is contemporary, even modern, and it definitely did not function as a defensive object. Due to its location at the edge of a manor house park it might have served as an observation mound, or was commemorative in character, honouring the victory of Prusy over Napoleon, or a visit of the governor of the area. It certainly functioned in minds of inhabitants as a man made object, which is undoubtedly confirmed by the word „burg” which occurred on a map from the beginning of our century. Surprising results of the research on the mound in Notyst provoked us to conduct preliminary examination of similar objects in the nearest surroundings (in Mlynik, Sorkwity commune, Kiersztanowo and Spiegel, near Mrągowo). In all the examined cases the origin of cone forms was anthropomorphic although there is no evidence of settlement layers (the function of a stronghold was thus excluded). In the neighbourhood a few objects of similar morphology, with hard to define function, have been also preserved. It seems that the occurrence of this type of objects in the subjected to penetration area deserves additional interest and further scientific research.